Virtual Character Design as a Replacement for Female YouTuber Figures - Adeline Linggar Mariela; Ayyub Hamdanu Budi Nurmana; Santi Widiastuti; Irdha Yunianto (Riwayat: Educational Journal of History and Humanities, 2025)
The development of the digital entertainment industry has given rise to the phenomenon of Virtual YouTubers as a new form of digital character representation that is increasingly in demand by global audiences. This research aims to design the virtual character design of female YouTubers as a replacement for female YouTubers who are able to attract the attention of the audience while strengthening the promotion strategy. The method used is Research and Development (RD) with the stages of needs analysis, design design, as well as limited and field trials. Data was obtained through observation, questionnaires, and validation by experts and peers, then analyzed descriptively based on character design theory, parasocial interaction, and fan economy. The results show that the consistency of visual identity is still a major challenge, while the technical limitations of rigging hinder the expressiveness of animation. On the other hand, merchandising strategies are considered effective in strengthening audience loyalty, and multi-stakeholder validation improves aesthetic quality and design legality. The field test also showed audience satisfaction with animation and merchandise as promotional media. In conclusion, the developed Virtual YouTuber character design has the potential not only as an entertainment medium, but also as a strategic instrument in digital promotion and fandom-based monetization. This research makes a theoretical contribution to the study of brand personality and fan economy, as well as a practical contribution in the form of an RD-based development model that can be adopted by small agencies in the digital creative industry.